Are immigrants more vulnerable to the socioeconomic impact of COVID-19? A cross-sectional study in Amadora Municipality, Lisbon metropolitan area - O. Martins, Maria Rosario; Shaaban, Ahmed Nabil; Abecasis, Ana; Muggli, Zelia; Amado, Regina; Vaz, Dora; Dias, Sara S.; Silva, Antonio C.; Fronteira, Ines (Frontiers in Public Health, 2022)
Introduction Immigrants carry an extra burden of morbidities and mortalities since the beginning of the coronavirus disease 2019 (COVID-19) pandemic. Pre-existing inequalities among immigrants may threaten their economic wellbeing during the pandemic. This study analyzed the socioeconomic impact of COVID-19 on immigrants and natives living in Amadora, Metropolitan Region of Lisbon and the extent to which preexisting inequalities had been exacerbated during the pandemic. Materials and methods This cross-sectional study was conducted in Amadora Municipality, Lisbon Region, through phone interviews and using a structured questionnaire. Data collected in July 2020, included information on a cohort of 420 households, of which 51% were immigrants. To evaluate the socioeconomic position and economic wellbeing changes occurring during the pandemic we estimate crude and adjusted odds ratio (OR) and 95% CI, using Portuguese natives as the reference group. Results Overall, 287 (70%) participants responded to the questionnaire, of which 47% are immigrants. Preexisting socioeconomic inequalities were exacerbated during the pandemic. Compared with natives, immigrants were more likely to experience job loss, temporary lay-off, and income loss during the COVID-19 pandemic. Immigrants were also more likely to face several kinds of financial hardship during the pandemic, such as difficulties in buying food, hygiene products, and paying bills. Conclusion To the best of our knowledge, this study is the first to capture the direct socioeconomic impact of COVID-19 among immigrants and natives in Portugal. It highlights the bidirectional relation between inequalities deeply rooted among immigrants and COVID-19. Socioeconomic inequalities affect local patterns of COVID-19 burden, as confirmed in previous studies, but COVID-19 also has an impact on the economic wellbeing of Amadora immigrants during the pandemic. Urgent policies must be implemented to mitigate the economic burden of COVID-19 among immigrants, namely in Amadora, Lisbon Region.